I got to know myself! Experience of a young drug user. - Peralta Barrientos , Jazmín de Fátima (2025)
Objective: Understanding the experience of a young drug user. Method: qualitative phenomenological study carried out in a young drug user selected at convenience. The data were collected through a phenomenological interview, the analysis was carried out using the Max Van Manen method. The study adhered to the ethical and legal aspects in force in research on human beings. Results: from the analysis of the discourses, the following categories emerged: 1) In/affective experiences of childhood: linked to family functionality, love, understanding and affection on the part of parents, 2) Addiction in transition: the evolution of the drug consumption, from alcohol to cocaine, 3) Reconstruction process: evidence of acceptance of the problem and the search for help through self-help groups. Conclusion: drug consumption in young people constitutes a health challenge, which requires an objective and subjective approach to the problem for the design of public health programs and policies.